A randomized study of very low‐dose factor VIII prophylaxis in severe haemophilia – A success story from a resource limited country. (14th March 2016) - Verma, S. P.; Dutta, T. K.; Mahadevan, S.; Nalini, P.; Basu, D.; Biswal, N.; Ramesh, A.; Charles, D.; Vinod, K. V.; Harichandra Kumar, K. T.
Abstract : Introduction: Current factor prophylaxis strategy practised in developed countries is not feasible in resource constraint developing countries like India. Aim: The aim of this study was to investigate the efficacy and safety of very low‐dose factor prophylaxis in India. Methods: Children of 1–10 years of age with severe haemophilia were randomized to Prophylaxis group and Episodic (On demand) group. Children in prophylaxis group received very low‐dose factor VIII (FVIII) concentrate, i.e. 10 units kg −1 body weights on 2 days a week. Episodic group received factor concentrate in standard recommended doses. The study period was 11.5 months. Results: In total 21 children were enrolled in this study, 11 assigned to prophylaxis and 10 to episodic group. Children on prophylaxis had 11 joint bleeds in comparison to 57 joint bleeds in episodic group. Mean number of haemarthrosis per patient per month were 0.08 (0.08 ± 0.13) in prophylaxis group compared to 0.48 (0.48 ± 0.34) in episodic group ( P < 0.05). Total FVIII consumption was 87.51 and 56.32 units kg −1 month −1 in prophylaxis and episodic group respectively ( P = ns). Overall median hospital emergency visits were 1 day in prophylaxis group and 9 days in episodic group ( P ≤ 0.05). Median days of absenteeism from school were 25 days in episodic group and 3 days in prophylaxis group ( P < 0.05). No significant complications were noted in prophylaxis group and compliance was 98%. Conclusion: To conclude, low‐dose FVIII prophylaxis is cost effective, efficacious and a safe method of preventing joint bleeds and consequent joint damages.